2019
DOI: 10.21009/ijhcm.03.01.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Commitment and Organizational Citizenship Behavior Toward Service Quality at Universitas Kristen Indonesia

Abstract: The objective of this research is to find out the effect organizational commitment and organizational citizenship behavior towards service quality at Universitas Kristen Indonesia. The research method used was a quantitative method wiht using path analysed design.  In collecting the data, 71 employees were chosen from 243 employees randomly to be the sample of this research. The data of the this research were obtained by distrubuting questiinnaires and analyzed them using path analysis. The result shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
2
4
0
3
Order By: Relevance
“…CSQ had a positive influence on OCB, especially when the level of frontline employees' CSQ is high, this enhances the morale of employees who then engage in continuous improvement, put in extra effort into satisfying customers, and help and volunteer for extra work. Our results are consistent with the findings of Siregar et al ( 2019 ), Khaskheli et al ( 2020 ), and Sumarsi and Rizal ( 2022 ) which demonstrated that frontline employees with higher CSQ accomplish given tasks better and behavior reflects OCB. The path modeling result relating to the third outcome of CSQ and turnover intention showed a significant negative relationship.…”
Section: Discussionsupporting
confidence: 93%
“…CSQ had a positive influence on OCB, especially when the level of frontline employees' CSQ is high, this enhances the morale of employees who then engage in continuous improvement, put in extra effort into satisfying customers, and help and volunteer for extra work. Our results are consistent with the findings of Siregar et al ( 2019 ), Khaskheli et al ( 2020 ), and Sumarsi and Rizal ( 2022 ) which demonstrated that frontline employees with higher CSQ accomplish given tasks better and behavior reflects OCB. The path modeling result relating to the third outcome of CSQ and turnover intention showed a significant negative relationship.…”
Section: Discussionsupporting
confidence: 93%
“…So, it can be given the meaning that the higher organizational commitment of employees will also increase the OCB of notary & PPAT employees in Bangli Regency. The results of this study are in line with the findings obtained by Hasani et al (2013), Prasetio et al (2015), Bazgir et al (2018), Bashir & Gani (2019), Siregar et al (2019), Fazriyah et al (2019), Wilkanandya & Sudarma (2020) who found that organizational commitment had a significant positive effect on OCB. While it is different from the findings obtained by Bone (2018), Grego-Planer (2019) who find that organizational commitment is not a significant positive effect on OCB.…”
Section: Discussionsupporting
confidence: 92%
“…Variations in the level of employee commitment are also determined by numerous factors, both organizational and individual factors (Junita, 2017;Bodjrenou et al, 2019;Bodjrenou et al, 2019;Parimita et al, 2020). The previous research findings support this, stating that organizational commitment could significantly contribute to employee OCB (Ardi & Sudarma, 2015;Fazio, 2015;Devece et al, 2016;Pigome et al, 2019;Siregar et al, 2019;Wilkanandya & Sudarma., 2020) but also not significant (Novianti, 2021).…”
Section: Organizational Citizenship Behaviormentioning
confidence: 60%
“…The way individuals perceive organizational situations also contributes significantly to employee organizational commitment. The previous research results (Ardi & Sudarma, 2015;Fazio, 2015;Devece et al, 2016;Pigome et al, 2019;Siregar et al, 2019;Wilkanandya & Sudarma., 2020) have also proven that there was a substantial contribution of organizational commitment in making employees' OCB more dominant. Hence, this phenomenon justifies this research to place organizational commitment as a mediating variable between organizational antecedents, i.e., organizational support and individual antecedents, namely emotional intelligence, on employee OCB.…”
Section: Junita Hafas and Nasutionmentioning
confidence: 78%